DETERMINASI AUDIT JUDGMENT: STUDI PADA BPK RI PERWAKILAN BALI: Analisis Faktor-faktor Penentu Keputusan Audit dalam Konteks Pemeriksaan Keuangan - Juliastini, Ni Putu; Komang, I Komang Trisna Eka Putra ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
This study aims to examine the influence of independence, professional ethics, timepressure, task complexity, internal locus of control and external locus of control on auditjudgment. The sample used was 40 auditors obtained by the saturated sample method. Theanalytical tool used is multiple linear regression analysis. The results of this study indicatethat the variables of independence, professional ethics, time pressure, and task complexitydo not affect audit judgment. Internal locus of control variables have a positive effect onaudit judgment, while external locus of control variables have a negative effect on auditjudgment.